2008
DOI: 10.1121/1.2999342
|View full text |Cite
|
Sign up to set email alerts
|

The role of temporal-masking patterns in the determination of subjective duration and loudness for ramped and damped sounds

Abstract: The association between temporal-masking patterns, duration, and loudness for broadband noises with ramped and damped envelopes was examined. Duration and loudness matches between the ramped and damped sounds differed significantly. Listeners perceived the ramped stimuli to be longer and louder than the damped stimuli, but the outcome was biased by the stimulus context. Next, temporal-masking patterns were measured for ramped-and damped-broadband noises using three ͑0.5, 1.5, and 4.0 kHz͒ 10 ms probe tones pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
53
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(62 citation statements)
references
References 28 publications
7
53
2
Order By: Relevance
“…However, loudness studies show that ramped sounds are perceived louder than damped sounds (e.g. Ries, Schlauch, & DiGiovanni, 2008). This contrast underscores that RT might not be an unconditional correlate of loudness.…”
Section: Discussionmentioning
confidence: 55%
“…However, loudness studies show that ramped sounds are perceived louder than damped sounds (e.g. Ries, Schlauch, & DiGiovanni, 2008). This contrast underscores that RT might not be an unconditional correlate of loudness.…”
Section: Discussionmentioning
confidence: 55%
“…We also did not measure whether, on average, sounds with different level profiles differed in loudness. A discussion of the latter question can be found in several studies comparing the loudness of ramped (i.e., containing a fade-in) and damped (i.e., decreasing in level across time) sounds (e.g., Neuhoff, 1998;Ries, Schlauch, & DiGiovanni, 2008;Stecker & Hafter, 2000;Susini et al, 2007). Finally, note that the task was not to discriminate between different level profiles, in the sense of deciding (for example) whether the sound had a flat level profile or contained a fade-in.…”
Section: Discussionmentioning
confidence: 99%
“…Major results have been achieved concerning the loudness asymmetries for a ramp duration of 1.8 s. However, recent results showed that the asymmetry still exists for longer durations (Ponsot et al, 2013). Up-ramps are also judged longer than down-ramps of the same physical duration (Schlauch et al, 2001;Grassi and Darwin, 2006;DiGiovanni and Schlauch, 2007;Ries et al, 2008;Grassi and Pavan, 2012). Most studies focused on the perceived duration asymmetry for durations shorter than 1 s. Globally it was found that the difference between the perceived duration of up-and down-ramps decreases as the duration increases from about 50 to 1000 ms (Schlauch et al, 2001;Grassi and Darwin, 2006;Ries et al, 2008;Grassi and Pavan, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…For example, when using ME, Schlauch et al (2001) found for a 1-kHz pure-tone, a ratio of about 4.5 for ramp duration of 25 ms that decreased to about 1.8 for ramp duration of 200 ms, while when using a matching procedure, they found a ratio of about 2.5 at 25 ms, which decreased to about 1.3 at 200 ms. In Ries et al (2008), with a broadband noise, the ratio decreased from 1.85 down to 1.2 for durations ranging from 50 to 500 ms. Some studies focused on short durations, i.e., <500 ms (Schlauch et al, 2001;DiGiovanni and Schlauch, 2007;Ries et al, 2008) while others focused on longer durations, i.e., from 250 ms to 2 s (Grassi and Darwin, 2006;Grassi and Pavan, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation